The Effect of Tender Coconut Water on Free Radical Due to Mercury Exposure - Siti Thomas Zulaikhah; Joko Wahyu Wibowo (Intelektual Pustaka Media Utama, 2018)
Mercury pollution can results from gold mining. Furthermore, a continuous mercury exposure can trigger the formation of Reactive Oxygen Species (ROS) and interfere with the body's antioxidant metabolism. A high level of free radicals in the body can be characterized by a low level of an antioxidant enzyme. Prevention to avoid the impacts of mercury poisoning is better than treatment. Tender coconut water can eliminate ROS and improve antioxidant status. This study aimed to was to confirm that tender coconut water is able to decrease the free radical which is characterized by increased antioxidant enzyme GPx status. This study was designed as randomized pre- and posttest control group design, 40 traditional gold mining workers devided into 2 groups: the control and treatment groups. After the pre test of GPx level, the workers were either given tender coconut water at the dose of 450 m L or water for 4 weeks every day. Four weeks after the pre-test, the level of GPx was assessed in the laboratory PAU-Gajahmada University. The post test results of the control group and treatments group were compared and analyzed using Man Whitney test. The mean levels of GPx post-test in the control group and treated group were 63.5±1.1 U/mL and 79.9±8.8 U/mL respectively. The analysis result obtained p-value 0.000 <0.05. Tender coconut water has an effect on free radicals due to to mercury exposure. Tender coconut water can be consumed daily to prevent degenerative diseases caused by mercury exposure.